WAYS TO SOLVE THE PROBLEMS OF RISK MANAGEMENT IN PROTECTING THE ASSETS OF COMMERCIAL BANKS - Absamatov Anvar Ergashevich (The Conference Hub, 2025)
As a result of the measures taken to deepen and expand the economic reforms being carried out in the banking system of our republic, special attention is paid to ensuring the financial stability of commercial banks, further increasing their capitalization, ensuring their broad participation in investment processes, structural reforms of the economy, modernization of production, technical and technological re-equipment, and strengthening their freedom.
Keywords: banking system, reforms, tasks, commercial banks, activity